2018
DOI: 10.30848/pjb2019-1(16)
|View full text |Cite
|
Sign up to set email alerts
|

Management of root rot diseases of eight wheat varieties using resistance and biological control agents techniques

Abstract: This study is focused on the screening of eight wheat varieties against Fusarium graminearum and Rhizoctonia solani root rot fungal diseases and their management through biological control agets (BCA) treatments under greenhouse conditions in Department of Plant Pathology, University of Nebraska, Lincoln (USA). These two soil-borne pathogens contributing to significant yield reduction and enhanced growth and yield of Wheat varieties (WVs) after BCA treatments. Experimental trails were set up by applying agar p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…caused diseases of seed rot and dampingoff. Ishtiaq et al (2019) indicated that R. solani fungus is a soil-borne fungus and causes a reduction in yield and causes a soft and dry weight reduction for the roots of wheat. The effect of pathogens on the seedlings may be due to its ability to produce a group of enzymes that cause the fall of these seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…caused diseases of seed rot and dampingoff. Ishtiaq et al (2019) indicated that R. solani fungus is a soil-borne fungus and causes a reduction in yield and causes a soft and dry weight reduction for the roots of wheat. The effect of pathogens on the seedlings may be due to its ability to produce a group of enzymes that cause the fall of these seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of plant diseases have been successfully controlled through fungal and bacterial antagonists (El-Ballat, 2017;Ishtiaq et al, 2019). El-Sayed-Sahar and Abdel-Monaim (2017) reported that biological control agents significantly reduced the disease severity of root rot diseases caused by Rhizoctonia and Fusarium.…”
Section: Separately Effect Of the Tested Fungicides And Bioagents On mentioning
confidence: 99%
“…They found that B. subtilis was the most effective bioagents followed by T. harzianum. The biological control agents secreted enzymes and secondary metabolites in wheat plants and induced systemic disease resistance against R. solani and F. graminearum (Ishtiaq et al, 2019). Table (3) reveal that T. harzianum moderately controlled the pathogens and then increased the percent of plant survivals which recorded 48.33 % for both pathogenic fungi when 4.5 × 10 6 spores mL -1 of T. harzianum were used.…”
Section: Separately Effect Of the Tested Fungicides And Bioagents On mentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat is prone to infection with many pathogens causing seed rot and damping-off diseases at different stages of plant growth ( Ishtiaq et al, 2019 ). Under field conditions, Chekali et al (2013) revealed that bread wheat and durum wheat cultivars seem to be susceptible to FRR but that some bread wheat cultivars had partial resistance.…”
mentioning
confidence: 99%